Complex Ankle Fusion With Circular Frames: Factors Influencing Outcomes, Complications, and Patient Satisfaction. (May 2023) - Tay, Kae Sian; Langit, Mickhael; Fenton, Carl; Grupping, Rachael; Muir, Ross; Moulder, Elizabeth; Sharma, Hemant
Background: Circular frames for ankle fusion are reserved for complex clinical scenarios. The literature is heterogenous and conflicting. We aim to present the indications and outcomes of this procedure. Methods: A retrospective cohort study based on a prospective database of frame surgeries performed in a tertiary institution. Inclusion criteria were patients undergoing complex ankle fusion with circular frames between 2005 and 2020, with a minimum 12-month follow-up. Data were collected on patient demographics, surgical indications, comorbidities, surgical procedures, external fixator time (EFT), length of stay (LOS), radiologic and clinical outcomes, and adverse events. Factors influencing radiologic and clinical outcomes were analyzed. Results: 47 patients were included, with a median follow-up of 30 months (interquartile range [IQR] 20-40). The median age at time of surgery was 63.5 years (IQR 58-71). Patients had a median of 2 previous surgeries (IQR 1-3). The median LOS was 8.5 days, and median EFT was 237 days (IQR 166-280). Simultaneous limb lengthening (median 3.3 cm, IQR 1.9-3.5) was performed in 11 patients, increasing the EFT by a mean of 4 months. Primary and final union rates were 91.5% and 95.7%, respectively. At last follow-up, ASAMI bone scores were excellent or good in 87.2%. ASAMI functional scores were good in 79.1%. Patient satisfaction was 83.7%. In addition, 97.7% of patients experienced adverse events, most commonly pin-site related, with major complications in 30.2% and reoperations in 60.5%. There were 3 amputations. Adverse events were associated with increased age, poor soft tissue condition, severe deformities, subtalar fusions, peripheral neuropathy, peripheral vascular disease, and prolonged EFT. Conclusion: Complex ankle fusion using circular frames can achieve good outcomes, however time in frame may be prolonged with a high rate of adverse events. Identified risk factors for poorer outcomes should be considered in patient counselling and prognostication. Level of Evidence: Level III, prognostic.